Association of the stress hyperglycemia ratio and clinical outcomes in patients with stroke: A systematic review and meta-analysis - Huang, Yong-Wei; Yin, Xiao-Shuang; Li, Zong-Ping (Frontiers in Neurology, 2022)
Objective Stress hyperglycemia (SH) is common in patients with acute diseases, such as stroke and myocardial infarction. Stress hyperglycemia ratio (SHR) is calculated by glucose/glycated hemoglobin and has been widely used for evaluating SH. But whether SHR is associated with clinical outcomes in stroke patients remains unclear so far. Although many studies have shown that higher SHR means poor outcomes, there is still no absolute evidence that SHR plays a critical role in stroke patients. Hence, we performed a systematic review and meta-analysis aiming to investigate the association between SHR and clinical outcomes in stroke patients. Methods We performed a comprehensive literature search of the PubMed, Embase, Cochrane Library databases, Clinicaltrials.gov, and WHO-ICTRP. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), we performed our study. The Newcastle-Ottawa Scale (NOS) tool was used to examine the potential bias of included studies. The endpoints including poor outcome, mortality, neurological deficit, hemorrhagic transformation (HT), and infectious complications were statistically analyzed. Results Sixteen retrospective studies met the eligibility criteria, and a number of 183,588 patients were included. Our meta-analysis demonstrated a significant increase in the incidence of poor outcome, according to assessment by the modified Rankin Scale (mRS) ≥ 3 points [odds ratio (OR) 2.53, 95% confidence interval (CI) 1.99–3.22, P < 0.00001, I2 = 68%], mortality (OR 1.96, 95% CI 1.58–2.44, P < 0.00001, I2 = 61%), neurological deficit (OR 1.99, 95% CI 1.47–2.70, P < 0.00001, I2 = 75%), hemorrhagic transformation (HT) (OR 3.70, 95% CI 2.69–5.08, P < 0.00001, I2 = 0%), and infectious complications [(Pneumonia) OR 2.06, 95% CI 1.57–2.72, P < 0.00001, I2 = 24%; (Urinary tract infection) OR 2.53, 95% CI 1.45–4.42, P = 0.001, I2 = 57%] in stroke patients with higher SHR. However, no significant influence was observed for recanalization rate (OR 0.86, 95% CI 0.54–1.38, P = 0.53, I2 = 0%). Conclusion With or without diabetes, no matter whether undergoing intravenous thrombolysis or mechanical thrombectomy, higher SHR significantly increased the occurrence of poor outcomes, mortality, neurological deficit, HT, and infectious complications. The recanalization rate was not statistically significant between the two groups. More attention must be paid in clinical practice to SH. Future investigation should focus on the diagnostic value of SHR and the early control of hyperglycemia. Meanwhile, whether SHR could become a novel and promising target for early intervention is worthy of attention in further research. Besides, the influence of the dynamic change of glucose-to-HbA1c ratio, namely SHR, on intracerebral hemorrhage outcomes requires further investigation in future research. Although no randomized double-blind studies have been conducted, the available massive sample studies reflect the actual situation in the clinic and assist clinical decision makers. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022345587.